Analisis Faktor yang Mempengaruhi Penunggakan Rekening Pembayaran Air pada PDAM Tirtanadi Sumut - Yuli Ekawati; Saparuddin Siregar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
PDAM Tirtanadi is a company engaged in the service and provision of clean water to the community, especially for the city of Medan and its surroundings. The operation of PDAM Tirtanadi itself is financed through sources of income received from PDAM Tirtanadi from customers who have used the services of PDAM Tirtanadi. However, on the other hand, the income that has been received by PDAM Tirtanadi is not as expected due to the high arrears of customers against PDAM Tirtanadi specifically for the surrounding terrain city. This study aims to be able to determine the factors that affect the payment of PDAM Tirtanadi Sumut. This research uses a descriptive method with a qualitative approach.